CNGC20 plays dual roles in regulating plant growth and immunity in Brassica napus - Yingying Tan; Guowei Huang; Haiyan Fan; Tao Wu; Zhilin Guan; Kede Liu (Crop Journal)
Inflorescence architecture is determined by inflorescence length, branch angles and the density of siliques, which affects planting density, lodging resistance and mechanical operation in rapeseed. However, the molecular mechanisms controlling inflorescence architecture are poorly understood, restricting the progress of breeding varieties with ideal plant architecture in oilseed rape. In this study, we have identified and characterized a rapeseed inflorescence development mutant, reduced inflorescence length (ril), which exhibits determinate and shortened inflorescences, reduced plant height, compact branches, and increased silique density. Through BSA-seq and map-based cloning, we find that RIL encodes a cyclic nucleotide-gated channel 20 (BnaA01.CNGC20). A substitution of proline at the 304th position to leucine (P304L) was identified in the conserved transmembrane domain of BnaA01.CNGC20. This P304L substitution neither affects the subcellular localization and self-assembly of BnaA01.CNGC20, nor disrupts the interactions with BRASSINOSTEROID INSENSITIVE 1-associated receptor kinase 1 (BAK1), which interacts with CNGC20 and phosphorylates it to regulate Ca2+ channel stability. However, the P304L substitution increases channel activity and Ca2+ influx, which in turn induces immune responses such as cell death, H2O2 accumulation, upregulation of pathogenesis-related genes, and pattern-triggered immunity. The enhanced immunity improves the resistance to Leptosphaeria biglobosa and Sclerotinia sclerotiorum. Transcriptome analysis further revealed that CNGC20 plays dual roles in regulating plant growth and immunity via the brassinosteroid and auxin signaling pathways. The findings in this study provide deeper insights into the intricate relationship between cytosolic Ca2+ level and plant development and immunity, as well as the trade-off between immunity and the performance of yield-related traits in the heterozygous plants (+/ril), which may serve as a guide for balancing yield and disease resistance in oilseed rape breeding.